Potency of Black Soybean (Glycine max (L.) Merr) Extract and Daidzein as Antioxidant and Antihyaluronidase - Tandiah Asan; I Nyoman Ehrich Lister; Edy Fachrial; Annisa Amalia; Wahyu Widowati; Buter Samin; Liena Liena (Majalah Obat Tradisional, 2019)
Black soybean (Glycine max (L.) Merr.) is a plant that is widely planted and consumed in Indonesia. In addition, black soybean has unique content of isoflavones, such as daidzein, which is one of the active compounds that have the effect of fighting free radicals and can inhibit the aging process. The purpose of this study is to analyze the antioxidant potency possessed by black soybean extract (BSE) and daidzeinin inhibiting aging of the skin. The method used is a colorimetric test. The type of antioxidant test used is H2O2 scavenging and inhibiting the activity of the hyaluronidase enzyme for antiaging. BSE has better effectiveness of H2O2 scavenging (IC50: 286.24±11.16 (µg/mL)) than daidzein compound (IC50: 366.16±2.54 (µg/mL)). In the inhibition of hyaluronidase enzyme, the daidzein has more effective activities (IC50: 95.80±3.98 (µg/mL)) compared to BSE (IC50: 152.56±13.98 (µg/mL)). The antioxidant and anti-aging activities possessed by BSE make it possible to be used as a cosmetic ingredient for skin aging therapy.